Endoscopic papillectomy for ampullary lesions: pooled analysis with meta-regression analysis of outcomes - Spadaccini, Marco; Franchellucci, Gianluca; Colombo, Matteo; Binda, Cecilia; Terrin, Maria; Marcozzi, Giacomo; Poletti, Valeria; Andreozzi, Marta; De Marco, Alessandro; De Sire, Roberto; Ramai, Daryl; Carrara, Silvia; Hassan, Cesare; Mangiavillano, Benedetto; Fugazza, Alessandro; Sethi, Amrita; Fabbri, Carlo; Facciorusso, Antonio; Anderloni, Andrea; Repici, Alessandro (Endoscopy)
Background: Endoscopic papillectomy(EP)is a viable treatment option for ampullary lesions(AL).While many studies have reported low morbidity and acceptable outcomes, early attempts to pool data from these initial experiences have produced conflicting conclusions regarding key technical aspects. To address these uncertainties, we conducted a systematic review and pooled analysis to evaluate the safety and effectiveness of EP for AL,identifying factors that may influence outcomes. Methods: Electronic databases(Medline, Scopus and EMBASE)were searched up to September 2024. Studies that included patients with endoscopically resected AL were eligible. Effectiveness and safety outcomes were pooled by means of a random-effects model to obtain a proportion with a 95% confidence interval(CI). Subgroup analysis, and univariable meta-regression analyses were conducted to explore potential factors affecting outcomes. Results: A total of 61 studies(4,935 lesions)published between 2002 and 2024 were analyzed. Complete resection was achieved in 85.9%of cases, though intraductal involvement limited success. The recurrence rate was 15.2%, however, the majority(92.4%)of patients were managed endoscopically without surgery. The pooled adverse event(AE)rate was 30.0%, with bleeding(12.8%)and post-procedural pancreatitis(11.2%)being the most common complications. Prophylactic stenting reduced pancreatitis risk, while intraductal involvement increased perforation risk.Adjunctive treatments for intraductal involvement posed an increased risk of papillary stricture. Conclusion: Endoscopic papillectomy is a safe and effective treatment for ampullary lesions. However, lesions with intraductal extension pose a higher risk of incomplete resection and perforation, warranting careful evaluation of the benefit-risk balance in these cases.While prophylactic pancreatic stenting may reduce the incidence of post-procedural pancreatitis, optimizing strategies to minimize overall adverse events remains a key focus for future research.